Transaction-cost economic analysis of institutional change toward design-build contracts for public transportation - Jan Whittington; David E. Dowall (University of California, Institute of Urban and Regional Development (IURD), 2006)
This research is a transaction-cost economic analysis of recently completed transportation projects, informing a comparative evaluation of the institutional change in public contracting from designbidbuild to designbuild project delivery. Designbuild, in which design and construction services are bundled together, is an alternative form of public contract recently adopted by transportation departments in more than 30 states. With this method, timely delivery arises from compact funding allocations and concurrent engineering. Such savings, however, may come at the expense of organized labor and environmental review, and could reflect higher transaction costs than traditional methods. At issue is the question of whether California 's Department of Transportation should also engage in designbuild contracting.
Keywords: 330; Öffentliche Beschaffung; Öffentlicher Bau; Verkehr; Transaktionskosten; USA